Setting Up a Medical Oncology Educational Program in Sub-Saharan Africa - Sara Bravaccini; Patrizia Serra; Dino Amadori; Mattia Altini; Nestory Masalu; Deogratias Katabalo; Lauro Bucchi; Carla Masini (Ubiquity Press, 2021)
One of the major problems facing healthcare systems in countries with poor socioeconomic conditions is the need to strengthen the system through the training of physicians, nurses and other healthcare operators. Partnering with more affluent countries is the key for hospitals in these areas, but such alliances are often based on limited educational exchanges. We present a retrospective study of our experience in building a collaborative relationship between our cancer institute in Italy and a Medical Center in sub-Saharan Africa (Tanzania). The main purpose is to see the changes in the clinical practice after educational interventions on health personnel in a Tanzanian cancer center.